Human Umbilical Cord Mesenchymal Stem Cells Promote Breast Cancer Metastasis by Interleukin-8- and Interleukin-6-Dependent Induction of CD44+/CD24- Cells. Issue 12 (December 2015) - Ma, Fengxia; Chen, Dandan; Chen, Fang; Chi, Ying; Han, Zhibo; Feng, Xiaoming; Li, Xue; Han, Zhongchao
Although emerging evidence links mesenchymal stem cells (MSCs) with cancer metastasis, the underlying mechanisms are poorly understood. In the present study, we found that human umbilical cord-derived MSCs (UC-MSCs) promoted MCF-7 cell migration in vitro and metastasis in vivo. To explore the mechanisms, the characteristics of MCF-7 cells cocultured with UC-MSCs were assessed. The expression and secretion of interleukin-8 (IL-8) and IL-6 were induced in MCF-7 cells cocultured with UC-MSCs. However, neutralization of IL-8 or IL-6 secreted by UC-MSCs could attenuate the enhanced expression of IL-8 and IL-6 in MCF-7 cells cocultured with UC-MSCs, which subsequently alleviated the enhanced migration. Similar to UC-MSCs, exogenous human recombinant IL-8 or IL-6 also promoted IL-8 and IL-6 expression and MCF-7 cell migration. In addition to enhanced IL-8 and IL-6 expression, MCF-7 cells cocultured with UC-MSCs displayed enhanced mammosphere-forming ability and increased percentage of CD44 + /CD24 - cells. However, epithelial-to-mesenchymal transition (EMT) was not observed in MCF-7 cells cocultured with UC-MSCs. Taken together, these results suggested that IL-8 and IL-6 secreted by UC-MSCs activated the autocrine IL-8 and IL-6 signaling in MCF-7 cells and induced CD44 + /CD24 - cells, which subsequently promoted MCF-7 cell migration in vitro and metastasis in vivo.